Percutaneous transcatheter pulmonary valve replacement in children weighing less than 20 kg. Issue 3 (29th November 2017) - Martin, Mary Hunt; Shahanavaz, Shabana; Peng, Lynn F.; Asnes, Jeremy D.; Riley, Michelle; Hellenbrand, William E.; Balzer, David T.; Gray, Robert G.; McElhinney, Doff B.
Abstract: Background: Since FDA approval of the Melody valve, transcatheter pulmonary valve replacement (TPVR) has been offered to an expanding population. Limited data exist regarding the safety and feasibility of TPVR in smaller patients. Methods: All patients weighing <20 kg who underwent catheterization for percutaneous TPVR at four centers were reviewed. Results: Of the 51 patients reviewed, 43 (84%) had successful valve implantation and 8 (16%) were found not to be candidates due to access veins too small ( n = 3), coronary artery/aortic root compression ( n = 3), and RVOT too large ( n = 2). The 43 patients who underwent successful percutaneous TPVR had a median age and weight of 5.8 years (3.3–10) and 17.7 kg (13.5–19.8), and most had tetralogy of Fallot (TOF). TPVR was performed via femoral vein (FV) access in 24 patients and internal jugular vein (IJV) access in 19 patients. Median weight in patients with IJV implant was 1.1 kg lower than those who underwent transfemoral implant (17.0 vs. 18.1 kg, P = 0.05). There were four adverse events: one iliac vein injury, one contained MPA tear, and two patients with post‐procedure femoral vein bleeding. All patients were alive at recent follow‐up, a median of 2.0 years (0.1–6.0) after TPVR. There was excellent valve function with mean Doppler gradients of 3–20 mm Hg, and trivial or mild pulmonary regurgitation in all but one patient. There were no RVOT reinterventions and no cases of endocarditis. Conclusions: Percutaneous TPVR can be safely performed in patients <20 kg. The procedure frequently requires IJV access, and access site/bleeding complications may be more common in this cohort.